Reliability Testing of Shingle-Matrix Modules in Glass-Glass Construction - Bauer, Marc-Philipp (PV-Symposium Proceedings, 2025)
Solar modules utilizing Shingle-Matrix-Technology present a promising opportunity for the future of European solar module manufacturers due to their technological benefits compared to the Asian mainstream [1]. To fully exploit their potential, Shingle-Matrix modules must demonstrate exceptional reliability. To assess their reliability, glass-glass Shingle-Matrix modules were manufactured, tested, and subjected to two years of outdoor exposure and standardized testing conditions in accordance with IEC 61215 [2]. The results were subsequently compared to modules with conventional architecture. The tested shingle-matrix-modules demonstrated resilience to the certification tests. By repeating and combining standard test routines beyond IEC the modules resilience was studied further. The Shingle-Matrix modules consistently yielded results that remained well within the established performance parameters. This outcome demonstrates the potential for a IEC certification-compliant market introduction, as demonstrated through the selected validation tests. The module's aesthetic design and shading resilience contribute to its suitability for building integrated photovoltaics (BIPV).